ANALISIS RISIKO KESEHATAN LINGKUNGAN KANDUNGAN TIMBAL (Pb) PADA KERANG HIJAU YANG DIKONSUMSI ISTRI NELAYAN DI TAMBAK LOROK, SEMARANG - Hapsari, Titi; Darundiati, Yusniar Hanani; Dangiran, Hanan Lanang (Fakultas Kesehatan Masyarakat, 2017)
Tambak Lorok is the largest fishing village in Semarang. Waters in Tambak Lorok contain Pb of 0.0781-0.288 ppm derived from activities in ports, fishing boats, domestic waste, and industrial waste. The purpose of this study is to analyze the risk of Pb content in perna viridis consumed by fisherman’s wife in Tambak Lorok. This study is an observational research with Environmental Health Risk Assessment approach. Population of this study is 130 perna viridis fisherman and the sample is 57 fisherman’s wife who consumed perna viridis in Tambak Lorok. Measurement of Pb in sea water on 3 sample points and green on 2 sample points. The calculation reveals that the concentration Pb of sea water at 1,2, and 3 points are <0,003mg/L, <0,003 mg/L, and 0,007 mg/L. The average Pb concentration of perna viridis is 0,45 mg/kg. The result of univariat analysis showed that the average weight of responden is 53 kg, with an average rate on intake is 255 gram/days, an average frequency of expossure is 102 days/year, an average duration of exposure is 11 years. The calculation of average realtime intake is 0,00025 mg/kg/days and average lifetime intake is 0,00067 mg/kg. The conclusion of this study isperna viridis in Tambak Lorok are still safe from non carsinogenik effects consumed in realtime and lifetime exposure (RQ<1).